Handbook of analog circuit design - Feucht, Dennis (Academic Press, 1990)
Handbook of Analog Circuit Design deals with general techniques involving certain circuitries and designs. The book discusses instrumentation and control circuits that are part of circuit designs. The text reviews the organization of electronics as structural (what it is), causal (what it does), and functional (what it is for). The text also explains circuit analyses and the nature of design. The book then describes some basic amplified circuits and commonly used procedures in analyzing them using tests of amplification, input resistance, and output resistance. The text then explains the feedback circuits-similar to mathematical recursion or to iterative loops in computer software programs. The book also explains high performance amplification in analog-to-digital converters, or vice versa, and the use of composite topologies to improve performance. The text then enumerates various other signal-processing functions considered as part of analog circuit design. The monograph is helpful for radio technicians, circuit designers, instrumentation specialists, and students in electronics.